An Analysis of the Emotive Interjections from The Interview Video Entitled "Stephanie Poetri Loves Playing the Sims and Is a Big Fan of Lauv"! - Sekar Lathifatul Aliyah (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2020)
This paper is aimed at the analysis of the emotive interjections from the interview video entitled "Stephanie Poetri Loves Playing the Sims and Is a Big Fan of Lauv!". Furthermore, it will explain the function of each emotive interjection that is found in the interview video. However, this paper uses quantitative and qualitative methods to support data analysis. Because the quantitative method will give information about the total number of the usage emotive interjections. Then the qualitative method is used for understanding the context of emotive interjection in the interview after collecting the total number of the data.